(untitled) (CIPEEX, 2022)
INTRODUCTION: CENTRAL VENOUS CATHETERS ARE ESSENTIAL IN HEALTH CARE AND ESPECIALLY IN PATIENTS ADMITTED TO INTENSIVE CARE UNITS, ALLOWING THE ADMINISTRATION OF MEDICINES AND / OR TRANSFUSIONS THROUGH THE PUNCTURE OF A LARGE CALIBER ACCESS. HOWEVER, ITS BENEFITS CAN CAUSE COMPLICATIONS, INCLUDING INFECTION OF THE BLOODSTREAM, LEADING TO HIGH MORBIDITY AND MORTALITY RATES, THUS PROLONGING THE TIME AND INCREASED COSTS OF HOSPITALIZATION. THESE INFECTIONS CAN BE PREVENTED BY INTERVENTIONS PERFORMED AT THE TIME OF CATHETER INSERTION AND DURING CATHETER INSERTION. OBJECTIVE: TO ANALYZE THE MEASURES ADOPTED BY HEALTH PROFESSIONALS TO PREVENT CENTRAL VENOUS CATHETER INFECTION IN THE INTENSIVE CARE UNIT. METHODOLOGY: INTEGRATIVE REVIEW OF THE LITERATURE, USING TEN ARTICLES FOUND IN THE VIRTUAL HEALTH LIBRARY, BETWEEN THE YEARS OF 2013 TO 2017 WITH THE DESCRIPTORS: VENOUS CATHETERIZATION, BLOODSTREAM INFECTION, NURSING. RESULTS: FOUR VENOUS CATHETERS WERE DIVIDED INTO FOUR CATEGORIES: CENTRAL VENOUS CATHETER, PROTOCOLS AND REGISTRIES, PREVENTION, TRAINING AND PATIENT SAFETY. FINAL CONSIDERATIONS: THE PREVENTION OF INFECTION RELATED TO THE USE OF THE CENTRAL VENOUS CATHETER DEPENDS DIRECTLY ON THE ASSISTANCE PROVIDED BY THE PROFESSIONAL TEAM, THE USE OF PROTOCOLS AND HEALTH EDUCATION ACTIONS, THUS IMPLEMENTING PREVENTIVE MEASURES AND CONTROL OF INFECTIONS RELATED TO THE CENTRAL.